Australian Trade Liberalisation Policy: The Industries Assistance Commission and the Productivity Commission. (June 2016) - Jones, Evan
The Productivity Commission is Australia's foremost policy advisory body. Its original incarnation as the Industries Assistance Commission derives from the 1960s push to dismantle the protective tariff regime that underpinned the Australian manufacturing sector. With success in tariff reductions and complementary reductions in rural sector assistance, the Commission's investigatory role was gradually expanded to cover the entire gamut of government policy. The Commission's history has generally been treated favourably. This article places the history of the original Industries Assistance Commission in context and takes a critical stance on its and the Productivity Commission's vision and achievements.